The Sexual Dimorphism of Lipid Kinetics in Humans - Santosa, Sylvia; Jensen, Michael D. (Frontiers in Endocrinology, 2015)
In addition to the obvious differences in body shape, there are substantial differences in lipid metabolism between men and women. These differences include how dietary fatty acids are handled, the secretion and clearance of very low-density lipoprotein-triglycerides, the release rates of free fatty acids (FFA) from adipose tissue relative to energy needs, and the removal of FFA from the circulation, including the storage of FFA into adipose tissue via the direct uptake process. We will review what is known about these processes and how they may contribute to the sexual dimorphism of body fat distribution.